2022
DOI: 10.1063/5.0113801
|View full text |Cite
|
Sign up to set email alerts
|

Study on the detonation reliability of explosive trains with a micro-sized air gap

Abstract: Air gap thickness significantly affects the detonation reliability of explosive trains. This paper mainly studies the detonation reliability of explosive trains with a micro-sized air gap. First, the detonation process of the JO-9C mild detonation cord initiating the 1.7 g/cm3 JO-11C booster is simulated by the AUTODYN software, and the critical air gap thickness is obtained between 0.32 and 0.40 mm. Second, a test device for explosive trains with adjustable air gap thickness is designed based on the numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Qiang et al [21] used a numerical model of the small-scale gap test to obtain the critical gas thickness for the detonation reaction of a solid propellant. Cheng et al [22] simulated the detonation process of explosive trains with a micro-sized air gap and concluded that the critical air gap thickness ranges from 0.32-0.40 mm. Following a series of underwater experiments, Xiao et al [23] concluded that COM B explosive charge can explode and has a peak pressure of 1600 MPa during launch with a bottom gap of 0.38 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Qiang et al [21] used a numerical model of the small-scale gap test to obtain the critical gas thickness for the detonation reaction of a solid propellant. Cheng et al [22] simulated the detonation process of explosive trains with a micro-sized air gap and concluded that the critical air gap thickness ranges from 0.32-0.40 mm. Following a series of underwater experiments, Xiao et al [23] concluded that COM B explosive charge can explode and has a peak pressure of 1600 MPa during launch with a bottom gap of 0.38 mm.…”
Section: Introductionmentioning
confidence: 99%